Inverse Association of Serum Docosahexaenoic Acid With Newly Diagnosed Hypertension: A Community-based Case-control Study. Issue 5 (February 2016) - Yang, Bo; Ding, Fang; Wang, Feng-Lei; Yu, Wei; Li, Duo
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Observational studies on circulating fatty acid (FA) and primary prevention of hypertension have yielded inconsistent results, and the association among the Chinese population is not fully clear. The aim of the study was to discern important FAs that can discriminate hypertensive patients from normotensive persons, and investigate associations between the important FAs and risk of hypertension. We conducted a case-control study nested within a community-based cohort of 2447 Chinese participants aged 35 to 79 years who completed a baseline assessment between October 2012 and April 2013. In all, 480 patients with newly diagnosed hypertension were identified at baseline and 480 normotensive individuals were randomly selected as matched normotensive controls. Controls were individually matched to cases by age (±2 y), sex, and recruitment center, with a 1:1 case-to-control ratio. Serum FA profile was compared between cases and controls by orthogonal partial least squares-discriminant analyses. Odds ratio (OR) with 95% confidence interval (CI) for newly diagnosed hypertension was estimated by a conditional logistical analysis. After adjustment for body mass index, education, profession, family history of hypertension, salt intake, heart rate, blood lipids, and fasting glucose levels, serum FA profile in hypertensive patients was typically characterized by higher 16:0 and 16:1n-7, and lower 18:2n-6 and 22:6n-3, compared with normotensive controls. Docosahexaenoic acid (22:6n-3) and palmitoleic acid (16:1n-7) were identified as the important FA contributing most to the intergroup separations. When comparing the highest and lowest quartile of FA composition, newly diagnosed hypertension was negatively associated with 22:6n-3 (OR 0.65; 95% CI, 0.45–0.93; P for trend = 0.02), but positively associated with 16:1n-7 (OR 2.14; 95% CI, 1.46–3.12; P for trend < 0.001). The associations remained pronounced after multiple adjustments and in further stratified analyses. In distinguishing hypertensive patients and normotensive persons, 22:6n-3 was considered as an important n-3 FA. Increased serum proportion of 22:6n-3 was associated with decreased odds of newly diagnosed hypertension, which suggests that high levels of 22:6n-3 in serum or perhaps in diet may be beneficial for prevention of hypertension in the Chinese population.